Mapping bedrock topography: a seismic refraction survey and landscape analysis in the Laramie Range, Wyoming - Uecker, Rachel Kaitlyn; Flinchum, Brady Adams; Holbrook, W. Steven; Carr, Bradley James (Frontiers in Water, 2023)
Physical, chemical, and biological processes create and maintain the critical zone (CZ). In weathered and crystalline rocks, these processes occur over 10s to 100s of meters and transform bedrock into soil. The CZ provides pore space and flow paths for groundwater, supplies nutrients for ecosystems, and provides the foundation for life. Vegetation in the aboveground CZ depends on these components and actively mediates Earth system processes like evapotranspiration, nutrient and water cycling, and hill slope erosion. Therefore, the vertical and lateral extent of the CZ can provide insight into the important chemical and physical processes that link life on the surface with geology 10s to 100s meters below. In this study, we present 3.9 km of seismic refraction data in a weathered and crystalline granite in the Laramie Range, Wyoming. The refraction data were collected to investigate two ridges with clear contrasts in vegetation and slope. Given the large contrasts in slope, aspect, and vegetation cover, we expected large differences in CZ structure. However, our results suggest no significant differences in large-scale (>10s of m) CZ structure as a function of slope or aspect. Our data appears to suggest a relationship between LiDAR-derived canopy height and depth to fractured bedrock where the tallest trees are located over regions with the shallowest depth to fractured bedrock. After separating our data by the presence or lack of vegetation, higher P-wave velocities under vegetation is a result of higher saturation.